2018
DOI: 10.1007/s00134-018-5342-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of frailty with short-term outcomes, organ support and resource use in critically ill patients

Abstract: Frailty, as assessed by MFI, was associated with several patient-centered endpoints including not only survival, but also ICU LOS and organ support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
100
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(113 citation statements)
references
References 28 publications
5
100
2
6
Order By: Relevance
“…Despite the ease of CFS application in critical care and its predictive validity [3,4], the relative advantages and disadvantages of CFS vs. other frailty assessment tools (e.g. frailty index generated from routinely collected data [18,20,21]) are underexplored in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the ease of CFS application in critical care and its predictive validity [3,4], the relative advantages and disadvantages of CFS vs. other frailty assessment tools (e.g. frailty index generated from routinely collected data [18,20,21]) are underexplored in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, such people have a lower chance of returning home with functional independence and have poorer quality of life if they survive the surgery and its complications . The 1‐year costs of care for such people were higher compared with costs for those who were not frail . This association of frailty with poor surgical outcomes appears to be independent of critical illness severity, suggesting that opportunities may exist to modify preoperative frailty and improve post‐operative outcomes.…”
Section: Frailty In Older People Undergoing Surgery: Prevalence and Amentioning
confidence: 99%
“…27 The effect of frailty on outcomes after elective surgery is increasingly described in hospital-based 24,25,[28][29][30][31] and population-based studies. 32,33 Outcomes such as increased mortality 31 especially after emergency surgery, 34 greater intensive care unit readmission rates, 26 longer hospital length of stay, 24,27,35 hospital readmission rates, 36 increased postoperative delirium 30 and other complications 35,36 occur more frequently in frail people undergoing surgery. A recent systematic review of nine observational studies of post-operative general surgical patients (n = 2241) identified higher 30-day mortality in frail group when compared to pre-frail group (8% versus 1%).…”
Section: Frailty In Older People Undergoing Surgery: Prevalence and Amentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to risk stratify critically ill patients and target intensive care unit resources to those who benefit the most is appealing and has resulted in a growing interest in the search for novel risk factors [1,2]. Performance status has gained significant attention recently [3,4]. In the same line, poor nutritional status, often judged by a low body mass index (BMI), is a prominent factor associated with poor short-and long-term outcomes [5,6].…”
mentioning
confidence: 99%